ANALISIS FITUR E-WADUL DEWAN DI SEKRETARIAT DPRD PROVINSI JAWA TENGAH DALAM PERSPEKTIF RESPONSIVE GOVERNANCE - Usman Alfarez, Rifky; Zarkasyi Rahman, Amni; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Responsive governance is the aspiration of all layers of society to support the principles of good governance. The Secretariat of the Regional House of Representatives (DPRD) of Central Java Province has introduced an innovation in the form of the E-Wadul Dewan service, which is a digital-based platform for the people of Central Java Province to submit complaints. The research problem formulated in this study is: How is the implementation of the E-Wadul Dewan feature of the Secretariat of the DPRD of Central Java Province from the perspective of responsive governance? This research uses a qualitative descriptive method. Furthermore, the analysis uses the responsive governance framework by Vij & Gil-Garcia (2017) and Maksimovska & Stojkov (2019). The findings of this research are as follows: First, the action plans to be implemented must be structured and integrated to provide appropriate responses to existing situations. However, there is a need to improve the capacity of the Public Relations staff of the Secretariat of the DPRD of Central Java Province. Second, although the E-Wadul Dewan has adopted SOP-based service standards, its validity is still minimal because the SOP used is only a basic concept and has not been officially ratified due to lengthy bureaucratic processes. Third, the method for measuring public satisfaction with the E-Wadul Dewan feature is based on the Community Satisfaction Index (IKM) with a score of 88.4 (satisfied). Fourth, the integration performed by E-Wadul Dewan includes system integration and coordination. Fifth, public complaint reports received can influence the policies planned by the Secretariat of the DPRD of Central Java Province through initiative regional regulations (Raperda). Sixth, inclusivity efforts are made by adding disability-friendly features to E-Wadul Dewan to accommodate these special groups. Therefore, it can be concluded that the use of the E-Wadul Dewan feature is quite responsive and aligns with the research framework. However, there are still some characteristics that can be improved